2011
DOI: 10.1002/term.347
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical characteristics of regenerated cortical bone in the canine mandible

Abstract: To test the mechanical properties of regenerate cortical bone created using Mandibular Bone Transport (MBT) distraction, five adult male American foxhound dogs underwent unilateral distraction of the mandible with a novel MBT device placed to linearly repair a 30-35 mm bone defect. The animals were sacrificed 12 weeks after the beginning of the consolidation period. Fourteen cylindrical specimens were taken from the inner (lingual) and outer (buccal) plates of the reconstructed mandible and 21 control specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 40 publications
(41 reference statements)
3
8
0
Order By: Relevance
“…This surgical process has been widely used not only because it has been shown that the quality of the new cortical bone created during the BTDO procedure resembles the original bone [26,31,32], but also because it allows early implants placement induced by the functional recovery of the mandible [33,34]. The present article provides evidence for a couple of biomechanical benefits of the mandibular BTDO process.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This surgical process has been widely used not only because it has been shown that the quality of the new cortical bone created during the BTDO procedure resembles the original bone [26,31,32], but also because it allows early implants placement induced by the functional recovery of the mandible [33,34]. The present article provides evidence for a couple of biomechanical benefits of the mandibular BTDO process.…”
Section: Discussionmentioning
confidence: 86%
“…A previous study from the authors reported the mechanical properties of the regenerate dog cortical bone are not only heterogeneous, but also tend to be approximately transversely isotropic at a tissue level as opposed to control cortical bone that is orthotropic [26]. Isotropic elastic moduli of the dog trabecular bone were obtained from the ultrasonic test of the femora of eight dogs [25].…”
Section: Methodsmentioning
confidence: 99%
“…A higher elastic modulus of cortical bone on the lingual side of the dog mandible was also found [32]. In humans, the buccal mandible hardness was found to be higher than in the maxilla [21].…”
Section: Discussionmentioning
confidence: 99%
“…Cortical bone apparent density (mg/cm 3 ) was calculated from the sample weight by using an analytical balance (PM460, Mettler-Toledo International INC, Columbus, OH, USA) and differential volume in water, based on Archimedes’ principle of buoyancy [27]. In addition, elastic mechanical properties were obtained for all specimens using an ultrasound test technique [16]. The direction of maximum strength was obtained with respect to the original reference line, and it was marked on the specimen by two notches that were clearly observed during three dimensional μ-CT reconstructions (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Although the biomechanical characteristics of the new bony tissue generated after DO have been addressed in different studies [12–15], only one previous study has focused on the mechanical properties of the new bone formed after BTDO [16], which showed a direct relationship between mechanical properties of cortical bone and its microstructure similar to Curry [17]. …”
Section: Introductionmentioning
confidence: 99%